2015
DOI: 10.1007/s00396-015-3681-x
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of superhydrophobic glass fiber-reinforced plastic surfaces with tunable adhesion based on hydrophobic silica nanoparticle aggregates

Abstract: The superhydrophobic glass fiber-reinforced plastic (GFRP) surfaces are prepared by spray coating a mixture on GFRP surfaces. The mixture is comprised of EPOLAM resin 2008 (EP2008), EPOLAM curing agent 2008-S (EP2008-S), hydrophobic silica nanoparticles (HSNPs), and acetone. By simply controlling the concentration of HSNPs in the mixture, the tunable adhesive superhydrophobic surfaces can be obtained. The results confirm that the as-prepared samples not only could achieve superhydrophobicity but also present h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Figure 1 and Figure 2 illustrate, respectively, the SEM images of the as-received and the etched AA 6082 surfaces at different times. According to [ 48 , 49 ], it can be observed that the etching time influences the surface morphology of the as-received aluminum substrates, promoting the transformation from a flat toward a micro/nano rough surface.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 and Figure 2 illustrate, respectively, the SEM images of the as-received and the etched AA 6082 surfaces at different times. According to [ 48 , 49 ], it can be observed that the etching time influences the surface morphology of the as-received aluminum substrates, promoting the transformation from a flat toward a micro/nano rough surface.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, seeking an effective way to mitigate the mechanical damage is really urgent. Not long ago, a few methods have been developed to tackle the mechanical damage problem [18][19][20][21][22] . By compression of the superhydrophobic metal particles, Larmour et al prepared superhydrophobic composite material with mechanical durability and easy repairability.…”
Section: Introductionmentioning
confidence: 99%